Genetic insights into dietary patterns, liposome mediation, and osteoporosis risk: a Mendelian randomization study - Kehan Long; Tengfei Zheng; Ao Gong; Zhendong Ying; Lei Zhang (Frontiers in Nutrition)
BackgroundThis study examines the indirect causal relationships between dietary habits and osteoporosis, mediated through liposomes, utilizing a two-sample Mendelian randomization (MR) approach. The research leverages genetic variations as instrumental variables to explore the genetic influences on dietary habits, liposomes, and osteoporosis, aiming to unravel the complex interplay between diet, lipid metabolism, and bone health.MethodsThe study utilized genome-wide association studies (GWAS) data for liposomes from Finnish individuals and osteoporosis-related data, alongside dietary factors from the OpenGWAS database. Instrumental variables were selected based on genetic variants associated with these factors, using a strict significance level and linkage disequilibrium threshold. Statistical analysis employed the Inverse Variance Weighted method, weighted median, and mode-based methods within the R environment, complemented by sensitivity analyses to ensure the robustness of the causal inferences.ResultsFindings revealed significant causal relationships between specific dietary components (white rice, cereal, and non-oily fish) and osteoporosis risk, both directly and mediated through changes in liposome levels. Notably, white rice consumption was associated with an increased risk of osteoporosis, while cereal and non-oily fish intake showed protective effects. Further, certain liposomes were identified as mediators in these relationships, suggesting a link between diet, lipid profiles, and bone health.ConclusionThe study highlights the significant impact of dietary habits on osteoporosis risk, mediated through liposomes. These findings underscore the importance of considering lipidomic profiles in dietary guidance and suggest potential targets for preventing osteoporosis through nutritional interventions.